Local dynamics of DNA probed with optical absorption spectroscopy of bound ethidium bromide. - Cupane, A (1997)
We have studied the local dynamics of calf thymus double-helical DNA by means of an "optical labeling" technique. The study has been performed by measuring the visible absorption band of the cationic dye ethidium bromide, both free in solution and bound to DNA, in the temperature interval 360-30 K and in two different solvent conditions. The temperature dependence of the absorption line shape has been analyzed within the framework of the vibronic coupling theory, to extract information on the dynamic properties of the system; comparison of the thermal behavior of the absorption band of free and DNA-bound ethidium bromide gave information on the local dynamics of the double helix in the proximity of the chromophore. For the dye free in solution, large spectral heterogeneity and coupling to a "bath" of low-frequency (soft) modes is observed; moreover, anharmonic motions become evident at suitably high temperatures. The average frequency of the soft modes and the amplitude of anharmonic motions depend upon solvent composition. For the DNA-bound dye, at low temperatures, heterogeneity is decreased, the average frequency of the soft modes is increased, and anharmonic motions are hindered. However, a new dynamic regime characterized by a large increase in anharmonic motions is observed at temperatures higher than approximately 280 K. The DNA double helix therefore appears to provide, at low temperatures, a rather rigid environment for the bound chromophore, in which conformational heterogeneity is reduced and low-frequency motions (both harmonic vibrations and anharmonic contributions) are hindered. The system becomes anharmonic at approximately 180 K; however, above approximately 280 K, anharmonicity starts to increase much more rapidly than for the dye free in solution; this can be attributed to the onset of wobbling of the dye in its intercalation site, which is likely connected with the onset of (functionally relevant) DNA motions, involving local opening/unwinding of the double helix. As shown by parallel measurements of the melting curves, these motions precede the melting of the double helix and depend upon solvent composition much more than does the melting itself.